Study on the saturation index of the carbonates in the groundwater using WATEQ4F, in layered coastal aquifers of Pondicherry - Chidambaram, S.; Prasanna, Mohan; Singaraja, C.; Thilagavathi, R.; Pethaperumal, S.; Tirumalesh, K. (Springer India Private Ltd., 2012)
A study was conducted to bring out the relationship and behavior of different Saturation Index (SI) of carbonate minerals in layered coastal aquifers. Carbonates present in groundwater aids in different nature of the water like hardness, partial pressure of carbon-di-oxide (pCO2), pH and saturation index of different carbonate minerals at various temperatures. The SI of the carbonates helps us to define the thermodynamic stability of water and to find out the geochemical behavior of water. 98 groundwater samples were collected from specific aquifers (alluvium, upper Cuddalore, lower Cuddalore and Cretaceous) during Pre-Monsoon (May 2007) and Post-Monsoon (January 2008) seasons. The physicochemical parameters such as pH, EC, Ca, Mg, Na, K, Cl, HCO3, SO4 and PO4 were analyzed. Geochemical model, WATEQ4F was used to calculate the SI of different minerals. The SI was studied in relation to mHCO3 concentration, pCO2 and correlation between SI of different minerals.